2012
DOI: 10.1248/bpb.b12-00118
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p53 and Nuclear Factor-kappaB Signaling Pathway for the Induction of G1-Phase Cell Cycle Arrest of Cholangiocarcinoma Cell Lines by Isomorellin

Abstract: Cell cycle arrest is closely linked to apoptosis. Isomorellin-a caged xanthone isolated from Garcinia hanburyi-induced apoptosis in cholangiocarcinoma (CCA) cell lines. To elucidate potential anticancer mechanisms, we investigated the effects of isomorellin on the growth, cell cycle progression, cell cycle regulated protein expression and nuclear factor-kappa B (NF-κB) activation of KKU-100 and KKU-M156 CCA cell lines; using sulforhodamine B assay, flow cytometry and Western blot analysis. The growth of both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…This may possibly be due to high levels of p21 in forbesione-treated cells causing downregulation of PCNA, which results in decreased tumor cell proliferation (47). The present results are consistent with those of our previous study (21), which demonstrated that the isomorellin-induced G 0 /G 1 phase cell cycle arrest of human CCA cell lines is mediated through inhibition of NF-κB activation, upregulation of p53, p21 and p27, and downregulation of cyclin D1, cyclin E, Cdk2 and Cdk4 protein expression. However, the mechanisms of cell cycle arrest induced by forbesione are only partially understood, and additional experiments are required to provide conclusive answers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This may possibly be due to high levels of p21 in forbesione-treated cells causing downregulation of PCNA, which results in decreased tumor cell proliferation (47). The present results are consistent with those of our previous study (21), which demonstrated that the isomorellin-induced G 0 /G 1 phase cell cycle arrest of human CCA cell lines is mediated through inhibition of NF-κB activation, upregulation of p53, p21 and p27, and downregulation of cyclin D1, cyclin E, Cdk2 and Cdk4 protein expression. However, the mechanisms of cell cycle arrest induced by forbesione are only partially understood, and additional experiments are required to provide conclusive answers.…”
Section: Discussionsupporting
confidence: 93%
“…KULTHIDA VAETEEWOOTTACHARN 3,6 and VICHAI REUTRAKUL selectively inhibited the proliferation of the human CCA cell lines KKU-100 and KKU-M156 by inducing apoptosis through the mitochondrial pathway (6), and by inducing G 0 /G 1 -phase cell cycle arrest through p53 and the nuclear factor (NF)-κB signaling pathway (21). Our previous studies demonstrated that combinations of isomorellin/doxorubicin and forbesione/doxorubicin exhibited significant synergy for inhibition of cell growth and induction of apoptosis in KKU-M156 and KKU-100 cells, respectively, through suppression of multidrug resistance-associated protein 1, NF-κB activation, enhanced expression of B-cell lymphoma (Bcl)-2-like protein 4 (Bax)/Bcl-2, activation of caspase-9 and caspase-3, and suppression of the expression of survivin, procaspase-9 and procaspase-3 (22).…”
Section: Antitumor Effect Of Forbesione Isolated From Garcinia Hanburmentioning
confidence: 99%
See 1 more Smart Citation
“…First, RAR␥ plays an active role in promoting cell proliferation and tumorigenicity, enhancing migration and invasion, and inducing multidrug resistance of CCA cells. Second, RAR␥ facilitated the G 1 /S transition; regulated P21 and cyclin D1, two critical cell cycle regulators (27); and upregulated the expression of the proliferation marker PCNA (28), which may contribute to tumor growth. Third, CCA is characterized by early metastasis (1), in which MMP-9 plays a critical role (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence has recommended that the ubiquitin-proteasome system plays a pivotal role in the cell cycle by mediating proteolysis [42]. Moreover, NF-kB has been considered as a critical modulator in the regulation of G 0 /G 1 cell cycle arrest [45]. In our study, CMT-3 significantly inhibited cyclin E expression instead of its transcription, indicating that the ubiquitin-proteasome system was probably involved in CMT-3-induced cell cycle arrest in Siha cells.…”
Section: Discussionmentioning
confidence: 99%